The Role Of Group Work Activities - Fatima Ergasheva Bakhrom kizi (Zien Journals, 2021)
This article discuss the role of group work activities and the importance motivating pupils through working in groups. There are also given some advantages of group work activities and life experiences.
Keywords: Collaboration; Profitable; Small-Group; Dominant